Узагальнений алгоритм розрахунку характеристик стратегій Клейнрока-Камоуна для розподілу буфера в мережах комутації пакетів - Ponomarenko, L. A.; Melikov, A. Z.; Fattahova, M. I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
Problem of buffer sharing between conflict traffics in message transfer systems with bufferisation were analyzed. Classic strategies of such sharing, offered by L. Kleinrock and F. Kamoun, were considered. A new approach to solving the problem of calculating characteristics in stochastic asynchronous message transfer systems, based upon principles of phase-aggregation states theory, is offered. Practical engineering formulas for calculating characteristics of the most general strategy is obtained.